Award Winner in the Young Investigator Category, 2017 Society for Biomaterials Annual Meeting and Exposition, Minneapolis, MN, April 05—08, 2017: Lymph node stiffness‐mimicking hydrogels regulate human B‐cell lymphoma growth and cell surface receptor expression in a molecular subtype‐specific manner. Issue 7 (12th April 2017) - Apoorva, F.N.U.; Tian, Ye F.; Pierpont, Timothy M.; Bassen, David M.; Cerchietti, Leandro; Butcher, Jonathan T.; Weiss, Robert S.; Singh, Ankur
Abstract: Diffuse large B‐cell lymphoma (DLBCL) is the most common type of non‐Hodgkin's lymphoma, with multiple molecular subtypes. The activated B‐cell‐like DLBCL subtype accounts for roughly one‐third of all the cases and has an inferior prognosis. There is a need to develop better class of therapeutics that could target molecular pathways in resistant DLBCLs; however, this requires DLBCLs to be studied in representative tumor microenvironments. The pathogenesis and progression of lymphoma has been mostly studied from the point of view of genetic alterations and intracellular pathway dysregulation. By comparison, the importance of lymphoma microenvironment in which these malignant cells arise and reside has not been studied in as much detail. We have recently elucidated the role of integrin signaling in lymphomas and demonstrated that inhibition of integrin‐ligand interactions abrogated the proliferation of malignant cells in vitro and in patient‐derived xenograft. Here we demonstrate the role of lymph node tissue stiffness on DLBCL in a B‐cell molecular subtype specific manner. We engineered tunable bioartificial hydrogels that mimicked the stiffness of healthy and neoplastic lymph nodes of a transgenic mouse model and primary human lymphoma tumors. Our results demonstrate that molecularly diverse DLBCLs grow differentially in soft and high stiffness microenvironments, which further modulates the integrin and B‐cell receptor expression level as well as response to therapeutics. We anticipate that our findings will be broadly useful to study lymphoma biology and discover new class of therapeutics that target B‐cell tumors in physical environments. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 1833–1844, 2017.